Death in delirious palliative-care patients occurs irrespective of age: A prospective, observational cohort study of 229 delirious palliative-care patients. Issue 3 (June 2021) - Seiler, Annina; Blum, David; Hertler, Caroline; Schettle, Markus; Zipser, Carl Moritz; Bode, Leonie; Gehrke, Samuel; Ernst, Jutta; Schubert, Maria; von Känel, Roland; Boettger, Soenke
Abstract: Objectives: Patients with terminal illness are at high risk of developing delirium, in particular, those with multiple predisposing and precipitating risk factors. Delirium in palliative care is largely under-researched, and few studies have systematically assessed key aspects of delirium in elderly, palliative-care patients. Methods: In this prospective, observational cohort study at a tertiary care center, 229 delirious palliative-care patients stratified by age: <65 ( N = 105) and ≥65 years ( N = 124), were analyzed with logistic regression models to identify associations with respect to predisposing and precipitating factors. Results: In 88% of the patients, the underlying diagnosis was cancer. Mortality rate and median time to death did not differ significantly between the two age groups. No inter-group differences were detected with respect to gender, care requirements, length of hospital stay, or medical costs. In patients ≥65 years, exclusively predisposing factors were relevant for delirium, including hearing impairment [odds ratio (OR) 3.64; confidence interval (CI) 1.90–6.99; P < 0.001], hypertension (OR 3.57; CI 1.84–6.92; P < 0.001), and chronic kidney disease (OR 4.84; CI 1.19–19.72; P = 0.028). In contrast, in patients <65 years, only precipitating factors were relevant for delirium, including cerebral edema (OR 0.02; CI 0.01–0.43; P = 0.012). Significance of results: The results of this study demonstrate that death in delirious palliative-care patients occurs irrespective of age. The multifactorial nature and adverse outcomes of delirium across all age in these patients require clinical recognition. Potentially reversible factors should be detected early to prevent or mitigate delirium and its poor survival outcomes.